"It Took Us a Long Time to Go Here": Creating Space for Young Children's Transnationalism in an Early Writers' Workshop. Issue 4 (29th November 2020) - Machado, Emily; Hartman, Paul
ABSTRACT: Although growing numbers of children engage in transnational literacy practices in their homes and communities, these practices are rarely invited into the early literacy classroom, where teachers face increasing pressure to standardize instruction. In this qualitative, participatory case study, we examined how one early literacy teacher created space for young children to explore transnationalism within his primary‐level writers' workshop. Drawing on theories associated with the trans ‐ turn in scholarship and using portraiture in analysis, we document how this teacher modified his published literacy curriculum to center students' translingual and transnational literacy practices. We also describe how three young children took up invitations to compose poetry that explored their transnational identities and experiences, highlighting how explorations of transnationalism enriched their writing. Ultimately, we suggest that early literacy teachers, including those working within the confines of increasingly standardized curricula, can create spaces for children to explore and express the fullness of their lives, including their transnationalism. We conclude with implications of this work for teaching and future research.